(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article discusses the role of the correctional police officer (policial penal) in contemporary society, highlighting his importance for public security, the challenges faced in the prison routine, and the need for greater recognition of this professional category. The study addresses the historical evolution of the function, from the former prison officer to the creation of the police career through Constitutional Amendment No. 104/2019. The paper analyzes the performance of these professionals in maintaining order inside prisons, as well as their indirect role in protecting society by preventing the influence of organized crime. Issues related to human rights, prisoner rehabilitation, and the psychological and social impacts experienced by correctional police officers are also emphasized. The conclusion points out that this professional plays an essential role in democracy, and that investments in recognition, infrastructure, and training are required so that their mission of protecting society can be fully achieved.